"Why do you dine at Korean restaurants?" An ethnic food consumption model approach. Issue 2 (4th March 2019) - Ha, Jooyeon
ABSTRACT: This study aimed to examine how people choose an ethnic restaurant based on the theory of planned behavior (TPB) to uncover factors that influence consumer decision-making in ethnic food consumption situations, particularly Korean food. Specifically, this study extended the original TPB model by incorporating consumer values and other variables that are theoretically related to the attitude formation, including familiarity and affective country image. The results showed that economic value, quality value, epistemic values, and familiarity were significant factors affecting consumer attitudes toward dining at Korean restaurants. Also, attitude, subjective norm, and perceived behavioral control significantly influenced consumer intentions to dine at Korean restaurants.